Ovarian maldescent: a case report and discussion - Mukherjee, Soma; R., Sanghamita; Bhartiya, Nandita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Undescended ovary or ovarian maldescent is a rare condition usually associated with mullerian malformation and typically found in case of infertility during their workup. Embryologically, the ovarian development from the genital ridge is totally different from the paramesonephric duct which forms the uterus and fallopian tubes. Still the ovarian maldescent has strong association with mullerian abnormalities, especially with unicornuate uterus. Therefore, supporting the hypothesis that abnormal migration could affect their normal fusion. In strong correlation of ovarian maldescent with mullerian abnormality here we report case of a patient presented to infertility clinic with unicornuate uterus with unilateral renal agenesis diagnosed to have unilateral undescended ovary with conclusion that the accurate diagnosis is important and radiological effort should be made to locate the undescended ovary if the ovary could not be found in normal location especially when associated with mullerian abnormality.